Effect of Maternal Nutrition and Micronutrient Supplementation on Neonatal Birth Weight and Health: Maternal Nutrition and Neonatal Health - Afridi, Sanodia; Joya, Sana Rehman; Inayat, Bela; Mariyum, Sara; Kalsoom, Ommia; Imtiaz, Hajra (Pakistan Journal of Health Sciences, 2025)
Maternal nutrition significantly influences fetal growth, birth weight, and neonatal health. Deficiencies in iron, calcium, folic acid, and vitamin D increase the risks of preterm birth, low birth weight, and neonatal complications. Objective: To assess the impact of maternal micronutrient supplementation on neonatal birth weight and health outcomes. Methods: A quasi experimental study was conducted at Health Net Hospital, Peshawar. A total of 110 pregnant women were recruited (59 supplemented, 51 non-supplemented). Data on maternal dietary intake, weight gain, and micronutrient consumption were collected. Neonatal birth weight, gestational age, NICU admissions, and morbidity were recorded. Statistical analysis was performed using SPSS version 25.0, with independent t-tests and chi-square tests (p<0.05 considered significant). Results: Neonates in the supplemented group had significantly higher birth weights (3343.54 ± 407.90 g vs. 2825.63 ± 322.46 g, p<0.001). NICU admissions were lower in the supplemented group (6.8% vs. 43.1%, p<0.001). Neonatal morbidity, including infections, jaundice, and respiratory distress, was significantly lower in the supplemented group (p<0.001). Conclusions: Micronutrient supplementation during pregnancy improves neonatal birth weight and reduces neonatal morbidity. These findings highlight the need for targeted maternal nutrition strategies to improve neonatal outcomes, particularly in resource-limited settings.